Kepercayaan terhadap Jimat di Labuhan Batu Utara: Studi Kritis dalam Perspektif Hadis - Isni Aulia Putri Sitorus; Muhammad Faishal (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The belief in amulets such as safety pins, scissors, bracelets, necklaces, and Yasin books as an antidote for pregnant women and babies is still growing in the community of Labuhan Batu Utara. This tradition is passed down from generation to generation and is believed to protect from the disturbance of spirits. This research aims to analyze the community's understanding of the use of amulets and examine the hadith view of the practice. The method used is a qualitative approach with a case study. Data were collected through field observations, in-depth interviews with local residents and religious leaders, and analysis of relevaMnt hadith literature. The results showed that some people use amulets as a form of protection for pregnant women and babies, although this practice is not in line with Islamic teachings. This finding makes it clear that the use of amulets contradicts the hadith which emphasizes that protection should come from Allah through prayer and tawakal, not from certain objects or symbols.